2012
DOI: 10.1016/j.ydbio.2012.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in vacuolar H+-ATPase subunits lead to biliary developmental defects in zebrafish

Abstract: Summary We identified three zebrafish mutants with defects in biliary development. One of these mutants, pekin (pn), also demonstrated generalized hypopigmentation and other defects, including disruption of retinal cell layers, lack of zymogen granules in the pancreas, and dilated Golgi in intestinal epithelial cells. Bile duct cells in pn demonstrated an accumulation of electron dense bodies. We determined that the causative defect in pn was a splice site mutation in the atp6ap2 gene that leads to an inframe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 59 publications
4
22
0
Order By: Relevance
“…The presence of skin and eye hypopigmentation in pn provided further evidence as this phenotype was previously associated with inhibition of the V-ATPase [21,22,24,25]. In the skin, melanoblast markers decreased with time which suggests that melanocytes developed normally but underwent degeneration [23]. In the eye, striking degradation of various cell layers was also observed.…”
Section: Zebrafishsupporting
confidence: 63%
See 1 more Smart Citation
“…The presence of skin and eye hypopigmentation in pn provided further evidence as this phenotype was previously associated with inhibition of the V-ATPase [21,22,24,25]. In the skin, melanoblast markers decreased with time which suggests that melanocytes developed normally but underwent degeneration [23]. In the eye, striking degradation of various cell layers was also observed.…”
Section: Zebrafishsupporting
confidence: 63%
“…These results suggested that (P)RR is important for embryonic development probably linked to V-ATPase activity but no direct evidence was provided by this animal model for years. Recently, Eauclaire et al performed a chemical mutagenesis screen to identify proteins important for biliary development [23]. Among all mutants with abnormalities in hepatic development, one mutant called pekin (pn) was particularly studied.…”
Section: Zebrafishmentioning
confidence: 99%
“…The in situ hybridization studies were performed essentially as described previously 13 , in accordance to standard protocols. PCR primers to generate riboprobes for ifng1-1 and ifng1-2 are shown in Supplementary Table S1.…”
Section: In Situ Hybridizationsmentioning
confidence: 99%
“…Expression QPCR studies were essentially performed as per previous studies, with primers (vhnf1, hprt) also used in previous studies. 13 For the methylation-specific QPCR (MSP), in silico analysis of sequence surrounding the transcription start site (-2.5 to + 0.5 kb) was performed using MethPrimer (http:// www.urogene.org/methprimer/), which identified putative CpG islands and methylated and unmethylated primers. MSP primers are also shown in Supplementary Table S1.…”
Section: Quantitative Pcrmentioning
confidence: 99%
See 1 more Smart Citation